Las interpretaciones de La casa de Bernarda Alba en los teatros húngaros en el siglo XXI - Katona, Eszter (Acta Hispanica, 2013)
Federico García Lorca's last play, The House of Bernarda Alba was in fact his first drama that waspresented to the Hungarian audience in the 1950s. Nearly sixty years have passed since then, andnumerous Hungarian theaters have included this play in their repertoire. I managed to trace 19 premiersfrom the period of 1955-2000 and 25 since the turn of the century. However, behind these high numberswe do not always find traditional theatrical presentations working with Lorca’s text. Other adaptations,like dance or musical plays, were also inspired by Lorca's drama, but with their different forms ofexpression they distinguished themselves from the traditional prose theater. Nevertheless, the presentation ofthese performances is important as well, as they contribute to the formation of Lorca's image in theHungarian audience. From these performances this study examines some of those from the first decade ofthe 21st century that, in some way, were significant, memorable or outstanding stagings.